Resistivity Characterization For Carbon Based Conductive Nanocomposite On Polyethylene Terephthalate And Thermoplastic Polyurethane Substrates - Salim, Mohd Azli; Ismail, Norhisham; Masripan, Nor Azmmi; Md. Saad, Adzni; Sudin, Mohd Nizam; Naroh, Azmi; Caridi, Francesco (Universiti Malaysia Perlis, 2020)
Nanotechnology has gained a lot of focus in recent years due to its application in multidisciplinary fields such as chemistry, electronics energy, and biology. Wearable electronic consists of nanocomposites liquid-solid conductive ink and flexible substrate. This study characterizes the electrical characteristic of the conductive ink with unloaded condition. The conductive ink was printed with four patterns; straight, curve, square and zig-zag patterns. Sheet and bulk resistivity results indicated the decrement of resistivity of all four patterns with the increase of the conductive ink width. From the result, it showed that the resistivity inside the conductive ink increased such as constriction resistance, tunnelling resistance and the number of squares of the meandering trace as compared to similar lengths of a straight-line trace. Size of the particle also affected the contact area and electrical flow between the conductive ink particles. Meanwhile, individual results for each pattern had its own function inside the circuit track